Effect of Antenatal Iron Supplementation on Rat Morphology - Umbreen Noor , Khadija Qamar ,Uzma Shahid , Irum Iqbal , Ifra Saeed, (Journal of Rawalpindi Medical College, 2012)
Background : To study the effect of routine antenatal daily iron supplementation on gross morphology of placenta. Methods: In this randomized control trial thirty two adult female and ten adult male Sprague- Dawley rats (weighing 200-250 gm) were taken. They were distributed randomly into two equal study groups. Ferrous sulphate was administered orally at 0 and 10mg/kg/day starting from gestation day (GD) 0, and half of the animals were sacrificed on GD 17 and half were sacrificed on GD 20. Placentae were removed and morphometric study was done for both qualitative and quantitative parameters. Results: The results were assessed on GD 17 and 20. There was no significant change in placental weight, diameter and thickness on GD 17 between the two groups. There was significant increase in placental weight, diameter and thickness on GD 20 in non-supplemented (control) rats as compared to iron replete rats. Conclusion: Antenatal daily iron supplementation is effective to prevent anaemia and iron deficiency.